Reproducibility of freehand vs. foam cast as well as the intrarater reliability of foam cast ultrasound scans assessing the muscle architecture and tissue organization of the gastrocnemius medialis and vastus lateralis muscles - Lesinski, Melanie; Bashford, Gregory; Markov, Adrian; Risch, Lucie; Cassel, Michael (Frontiers in Sports and Active Living, 2024)
Background This study compares the reproducibility of freehand (FH) vs. foam cast (FC) scans and investigates the intrarater reliability of the ultrasound FC muscle architecture and tissue organization measurements of the gastrocnemius medialis (GM) and vastus lateralis (VL) muscles with fixed and repositioning FC scans. Methods Thirteen young adults (22 ± 3 years) underwent repeated sagittal B-mode ultrasound measurements of GM and VL. FH, FC, and repositioned FC scans were conducted. Muscle architecture measurements included muscle thickness (MT), pennation angle (PA), and fascicle length (FL). Spatial frequency analysis assessed muscle tissue organization. Results MT decreased from 2.1 to 1.8 cm in GM and from 2.4 to 2.2 cm in VL with the FC compared with the FH. Reproducibility between the FH and the FC showed poor to good intraclass correlation coefficients (ICCs) for MT (0.46–0.77) and PA (0.09–0.86) as well as poor to moderate ICCs for FL (0.41), with very low to moderate test–retest variability (TRV) (4%–18%). Tissue organization indicated low to good ICCs (0.21–0.80) with low to moderate TRV (4%–19.5%). The re-scanning results of fixed FC indicated excellent ICCs for MT (0.95–0.996), good for PA (0.77–0.90), and moderate for FL (0.73–0.76), with low TRV (5%–10%) for both muscles. Tissue organization displayed moderate to good ICCs (0.61–0.87) with very low to low TRV (4%–9%). For repositioned FC scans in GM and VL, MT showed good to excellent ICCs (0.86–0.98) with very low to low TRV (2%–8%). PA and FL demonstrated moderate to good ICCs (0.57–0.75), with very low to moderate TRV (2%–13%). Tissue organization revealed ICCs ranging from poor to good (0.13–0.87) for both muscles, with low to moderate TRV (5%–18%). Conclusion The FC systematically reduced MT by 2–3 mm. Furthermore, reproducibility revealed low ICCs and high data variability for several muscle architecture and tissue organization parameters. Thus, switching methods within a single study is not recommended. Nevertheless, FC ultrasound scans demonstrated excellent intrarater reliability for assessing MT. In the case of fixed FC scans particularly, moderate to excellent ICCs were observed for all muscle architecture and tissue organization parameters, accompanied by very low to low variability. Therefore, FC scans are recommended for investigating acute effects on muscle architecture and tissue organization when the FC remains on the leg throughout the period of measurements.